LC–MS/MS glycomics of idiopathic rapid eye movement sleep behavior disorder. Issue 24 (12th September 2018) - Dong, Xue; Mondello, Stefania; Kobeissy, Firas; Talih, Farid; Ferri, Raffaele; Mechref, Yehia
Abstract: Idiopathic REM sleep behavior disorder (iRBD) is now considered a prodromal stage of an α‑synucleinopathy‐related to neurodegenerative disease such as Parkinson's diseases. Emerging evidence has shown that post‐translational modification or glycosylation are implicated in dynamic disease mechanisms and the onset of many pathological conditions. We hypothesized that the characterization of the glycosylation pattern of patients with RBD would be of great value to understand the pathophysiology and underlying mechanisms and represent potentially useful biomarkers for disease‐associated molecular changes. To test this hypothesis, we assessed the serum glycome of patients with RBD and compared to that of healthy controls. NanoRPLC–MS was used to generate quantitative N‐glycan profiles while high‐temperature PGC‐LC–MS platform was employed to generate quantitative isomeric N‐glycan profiles. By analyzing permethylated glycans derived from human blood sera on C18‐LC–MS/MS, we identified 59 N‐glycan structures in healthy (control) cohort, 56 N‐glycans in RBD cohort. Sixteen N‐glycans structures were found to be significantly altered in the RBD cohort ( p  < 0.05). N‐glycans with the composition of HexNAc4 Hex5 Fuc1, HexNAc5 Hex5, and HexNAc4 Hex5 Fuc1 NeuAc1 presented the most substantial difference between controls and RBD patients ( p  < 0.01). HexNAc4 Hex5 Fuc1 NeuAc1 showed a relatively high abundance (3.1 ± 0.7% in the control cohort versus 4 ± 3% in the idiopathic RBD cohort). These N‐glycans can be potential diagnostic biomarker candidates and provide a window into underlying neurodegenerative processes in patients with idiopathic RBD. In addition, 7 N‐glycan isomers were significantly different between controls and RBD patients ( p  < 0.05). HexNAc4 Hex5 Fuc1 NeuAc1 (4511‐2) and HexNAc4 Hex5 Fuc1 NeuAc2 (4512‐2) showed the most substantial difference between the control and idiopathic RBD cohorts ( p  < 0.001). Levels of both these two isomeric structures were higher in the idiopathic RBD cohort. Further larger studies are required to assess the reproducibility of these findings and to elucidate the role played by the changes in glycan structures in the pathogenetic mechanisms of RBD. This information will be instrumental in developing molecular therapeutic targets to promote neuroprotection and prevention of neurodegeneration.